Feasibility of implementing routine nutritional screening for older adults in Australian general practices: a mixed-methods study - Hamirudin, Aliza Haslinda; Charlton, Karen; Walton, Karen; Bonney, Andrew; Potter, Jan; Albert, George; Milosavljevic, Marianna; Hodgkins, Adam; Ghosh, Abhijeet; Dalley, Andrew (BioMed Central, 2014)
Nutrition screening in older adults is not routinely performed in Australian primary care settings. Low awareness of the extent of malnutrition in this patient group, lack of training and time constraints are major barriers that practice staff face. This study aimed to demonstrate the feasibility of including a validated nutrition screening tool and accompanying nutrition resource kit for use with older patients attending general practice. Secondary aims were to assess nutrition-related knowledge of staff and to identify the extent of malnutrition in this patient group